A Comparative Evaluation of IP Geolocation Services for Brazilian Data Enrichment - Vieira, Pedro G. B.; Costa, Lucas G. L.; Pappa, Gisele L. (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2026: Anais do XLI Simpósio Brasileiro de Bancos de Dados, 2026)
IP geolocation information is fundamental for enhancing analytical datasets, supporting applications such as recommendation systems, investigation, service personalization, among others digital fields. However, there are several geolocation discovery free online services as database enrichment tools. This work evaluate several of those services, aiming to define the most reliable service for the Brazilian network context, and compares their performance across IPv4 and IPv6. The ground truth set is extracted from Ripe Atlas’s brazilians devices. The experiment shows that BigData Cloud is the best service and have better results with IPv6 results. Despite the inherent limitation in obtaining reliable IP-based geolocation data, these findings help practitioners select more reliable services for geolocation enrichment of Brazilian IP datasets.